(untitled) (Medico Legal Update, 2019)
The purpose of this study was to investigate the effect of body mass index (BMI) on muscle strength and activity according to the knee angle. Muscle activity of vastus medialis (VM), vastus lateralis (VL), and rectus femoris (RF) was measured for 48 healthy adults. Isokinetic equipment was used to measure the isometric strength of the knee extensors at 0°, 30°, 60°, and 90° flexion. One-way ANOVA was used to compare isometric muscle strength and activity. The maximum isometric strength of the knee extensors according to the knee angle showed a significant difference between the groups at 0°, 30°, and 90° of knee flexion (p<.05). The maximum isometric strength at 0° flexion of the knee joint was significantly different between the normal and overweight, and the underweight and overweight, respectively. In knee flexion 30°, there was a significant difference between underweight and normal, underweight and overweight. In 90° flexion, there was a significant difference between the underweight and the overweight. There was a significant difference in VM at 0° and 30° knee flexion (p < .05). Post hoc test results showed a significant difference between underweight and overweight at 0° flexion. In 30° flexion, there was a significant difference between normal and overweight, and between underweight and overweight. It is considered that selective muscle strengthening according to a specific angle is necessary according to BMI.